Stability analysis and persistence of a phage therapy model - Ei Ei Kyaw (AIMS Press, 2021)
This study deals with a phage therapy model involving nonlinear interactions of the bacteria–phage–innate immune response. The main aim of this work is to analytically and numerically examine the dynamic behavior of the phage therapy model. First, we investigate the positivity and boundedness of the system. Second, we analyze the existence and local asymptotic stability of different equilibrium solutions. Third, we investigate the global stability for equilibrium without immune system and equilibrium without phages, and coexistence equilibrium by means of the Bendixson–Dulac criterion and the Lyapunov functional method, respectively. Furthermore, we discuss the persistence and nonpersistence of the system under some conditions. Finally, we perform numerical simulations to substantiate the results obtained in this research.